2020
DOI: 10.1007/s11101-020-09715-3
|View full text |Cite
|
Sign up to set email alerts
|

Rheum rhaponticum and Rheum rhabarbarum: a review of phytochemistry, biological activities and therapeutic potential

Abstract: The Rheum genus (Polygonaceae) covers about 60 species of rhubarbs, including specimens with a long ethnomedicinal history in Asia, Europe and other regions of the world. The work reviews available literature (until March, 2020) on phytochemical profile, ethnomedicinal recommendations, biological activities, pharmacological uses and future prospects for therapeutic applications of Rheum rhabarbarum L. (garden rhubarb) and Rheum rhaponticum L. (rhapontic rhubarb). Although the above species are well-known veget… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 100 publications
0
27
0
2
Order By: Relevance
“…The antibacterial properties of plants have been widely investigated [ 3 ]. In fact, a great variety of plant species containing components which exhibit antimicrobial activity against a wide range of Gram-positive and Gram-negative bacteria has been reported, including Hibiscus , Rosmarinus officinalis , Thymus vulgaris , Malva sylvestris and Allium sativum , among others [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. Plant antimicrobials are more attractive than the synthetic food preservatives, as they are generally recognized as safe and capable of benefiting human health, including essential oils [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The antibacterial properties of plants have been widely investigated [ 3 ]. In fact, a great variety of plant species containing components which exhibit antimicrobial activity against a wide range of Gram-positive and Gram-negative bacteria has been reported, including Hibiscus , Rosmarinus officinalis , Thymus vulgaris , Malva sylvestris and Allium sativum , among others [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. Plant antimicrobials are more attractive than the synthetic food preservatives, as they are generally recognized as safe and capable of benefiting human health, including essential oils [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Petiole color is associated with rhubarb quality and the order of preference is red, pink, and green [ 2 ]. Although rhubarb is a well-known vegetable, scientific interest in this plant is a relatively new issue; most of the evidence of its biological activities and therapeutic potential derives from the last 15 years [ 4 ]. It shows high levels of both polyphenol content and antioxidant capacity in edible parts [ 5 ], which are petioles characterized by very high antioxidant properties and rich in many compounds that have a pro-health effect on the human body [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The main characteristics of rhubarb quality are taste and aroma, which depend on the chemical composition [ 9 ]. Studies on the phytochemical composition of different species of rhubarb have provided information on the presence of a variety of inorganic and organic acids (including tartaric, oxalic, citric, malic, and ascorbic acids) [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…This indicated that the extract's effect was dictated by the high components of the extracts, as shown in another experiment that found a positive correlation between the content and the effects. [ 13 14 15 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 24 ] The mechanism of Rheum extract in bone calcium has not been elucidated yet, but rhaponticin that contained in Rheum extract has a similar molecular structure with tamoxifen; they have a stilbenoid group. [ 15 25 ]…”
Section: Discussionmentioning
confidence: 99%